2011
DOI: 10.1016/j.rmed.2011.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Transition of asthmatic bronchial fibroblasts to myofibroblasts is inhibited by cell–cell contacts

Abstract: The role of airway wall remodelling in bronchial asthma is well established. Myofibroblasts, the cells displaying features intermediate between fibroblasts and smooth muscle cells, are involved in this process but the mechanism of myofibroblasts activation in the onset of the disease remains obscure. Myofibroblasts can differentiate from various cell types, including resident fibroblasts, and the fibroblasts to myofibroblasts transition (FMT) can be reproduced in vitro. We aimed to investigate the process of F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 39 publications
3
52
0
Order By: Relevance
“…We have previously demonstrated that HBFs derived from patients with bronchial asthma display inherent features in vitro that facilitate FMT in response to prolonged incubation with TGF- β 1 [14, 34]. Here, we aimed to investigate the interference of lithium with TGF- β 1 -induced FMT in HBF populations derived from asthmatic patients (AS, n = 8) and non-asthmatic subjects (NA, n = 8).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously demonstrated that HBFs derived from patients with bronchial asthma display inherent features in vitro that facilitate FMT in response to prolonged incubation with TGF- β 1 [14, 34]. Here, we aimed to investigate the interference of lithium with TGF- β 1 -induced FMT in HBF populations derived from asthmatic patients (AS, n = 8) and non-asthmatic subjects (NA, n = 8).…”
Section: Resultsmentioning
confidence: 99%
“…Primary HBF were isolated from bronchial biopsies as described previously [14, 34]. The first group consisted of patients with moderate to severe bronchial asthma (AS group) with a mean age of 43.1 ± 9.5 years (females 64%), the average duration of the disease was 11.3 ± 9.4 years, and decrease in the first second forced expiratory volume (FEV1: 78.4 ± 22.4% of predicted).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, MF differentiation is regulated by the combination of specific cells and a series of ECM molecular components [20,21,22]. Cell-cell contacts [23] and mechanical force transductions [24,25,26,27] participate in the process.…”
Section: Introductionmentioning
confidence: 99%